DETERMINANTS OF DIGITAL MARKETING ADOPTION BY MSMES: A UTAUT2 PERSPECTIVE IN PONTIANAK - Wendy Suhendry; Fera Maulina (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study examines the determinants of use behavior toward digital marketing among MSMEs in Pontianak using the UTAUT2 framework—Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, Habit, and Facilitating Conditions.METHODOLOGY - A cross-sectional survey of N = 100 owners/managers employed an adapted UTAUT2 instrument. Item validity and reliability were satisfactory (all item–total correlations > .80; Cronbach’s α for predictors = .84, Use Behavior = .87). Classic assumption tests were met. Data were analyzed using multiple linear regression.FINDING - The model is significant with R = 0.60, R² = 0.36 (Adjusted R² = 0.32). Positive, significant predictors of Use Behavior are Social Influence, Habit, and Facilitating Conditions. Performance Expectancy, Effort Expectancy, and Hedonic Motivation are not significant when entered jointly.